2001
DOI: 10.1101/lm.39401
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Expressed in the Amygdala During the Formation of Fear Memory

Abstract: In this study we describe changes of gene expression that occur in the basolateral complex of the mouse amygdala (BLA) during the formation of fear memory. Through the combination of a behavioral training scheme with polymerase chain reaction-based expression analysis (subtractive hybridization and virtual Northern analysis) we were able to identify various gene products that are increased in expression after Pavlovian fear conditioning and are of potential significance for neural plasticity and information st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 46 publications
3
59
0
Order By: Relevance
“…PCR-based gene expression analysis confirmed that Ndr2 transcript levels were transiently elevated in the amygdala of fear-conditioned and pseudo-conditioned animals 6 h after training and returned to baseline within 24 h. Thus, during consolidation of fear memory, Ndr2 mRNA levels are regulated in the basolateral complex of the amygdala in a learning-and stress-dependent manner, similar to several other signal transduction and structural re-organization factors (2). GenBank TM analysis suggests that transcription of the Ndr2 gene may be driven through cyclic AMP response elements (CRE) or serum-responsive elements.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…PCR-based gene expression analysis confirmed that Ndr2 transcript levels were transiently elevated in the amygdala of fear-conditioned and pseudo-conditioned animals 6 h after training and returned to baseline within 24 h. Thus, during consolidation of fear memory, Ndr2 mRNA levels are regulated in the basolateral complex of the amygdala in a learning-and stress-dependent manner, similar to several other signal transduction and structural re-organization factors (2). GenBank TM analysis suggests that transcription of the Ndr2 gene may be driven through cyclic AMP response elements (CRE) or serum-responsive elements.…”
Section: Discussionmentioning
confidence: 65%
“…1A) was selected from a group of 21 gene products that were differentially expressed in the amygdala during consolidation of fear memory (2). As the first step in our analysis, the induction of Ndr2 expression was confirmed with PCR-based Northern analysis on amygdala samples pooled from each group of four animals (2) (Fig.…”
Section: Isolation and Differential Expression Of Ndr2-mentioning
confidence: 98%
See 3 more Smart Citations